Comparative Transcriptome Analysis Reveals Gene Expression Differences in Eggplant (Solanum melongena L.) Fruits with Different Brightness - Aidong Zhang; Qianru Huang; Jianyong Li; Weimin Zhu; Xiaohui Liu; Xuexia Wu; Dingshi Zha (Foods, 2022)
Fruit brightness is an important quality trait that affects the market value of eggplant. However, few studies have been conducted on eggplant brightness. In this study, we aimed to identify genes related to this trait in three varieties of eggplant with different fruit brightness between 14 and 22 days after pollination. Using RNA-Seq Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses, we found that wax- and cutin-related pathways and differentially expressed genes displayed significant differences among different development stages and varieties. Scanning electron microscopy revealed that the wax layer was thinner in ‘30-1’ and ‘QPCQ’ than in ‘22-1’. Gas chromatography-mass spectrometry analysis revealed that wax content was significantly lower in ‘30-1’ than in ‘22-1’, which indicated that wax may be an important factor determining fruit brightness. We further identified and analyzed the KCS gene family, which encodes the rate-limiting enzyme of FA elongation in wax synthesis. The results provide an insight into the molecular mechanisms of fruit brightness in eggplants and further eggplant breeding programs.